2015
DOI: 10.3389/fpsyg.2015.01908
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Styles Myth is Thriving in Higher Education

Abstract: The existence of ‘Learning Styles’ is a common ‘neuromyth’, and their use in all forms of education has been thoroughly and repeatedly discredited in the research literature. However, anecdotal evidence suggests that their use remains widespread. This perspective article is an attempt to understand if and why the myth of Learning Styles persists. I have done this by analyzing the current research literature to capture the picture that an educator would encounter were they to search for “Learning Styles” with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
1
26

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(134 citation statements)
references
References 13 publications
5
102
1
26
Order By: Relevance
“…Participants were then asked “have you ever administered a Learning Styles questionnaire to your students” and were given four specific examples along with the ‘styles’ identified by those examples. The examples chosen were those most commonly found in a recent study of the literature on Learning Styles (Newton, 2015). Participants were also given the option to check ‘other’ and identify any other types of Learning Styles questionnaire that they might have used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were then asked “have you ever administered a Learning Styles questionnaire to your students” and were given four specific examples along with the ‘styles’ identified by those examples. The examples chosen were those most commonly found in a recent study of the literature on Learning Styles (Newton, 2015). Participants were also given the option to check ‘other’ and identify any other types of Learning Styles questionnaire that they might have used.…”
Section: Resultsmentioning
confidence: 99%
“…A study of Higher Education faculty in the USA showed that 64% agreed with the statement “Does teaching to a student’s learning style enhance learning?” (Dandy and Bendersky, 2014). A recent study demonstrated that current research papers ‘about’ Learning Styles, in the higher education research literature, overwhelmingly endorsed their use despite the lack of evidence described above (Newton, 2015). Most of this endorsement was implicit and most of the research did not actually test Learning Styles, rather proceeded on the assumption that their use was a ‘good thing.’ For example, researchers would ask a group of students to complete a Learning Styles questionnaire, and then make recommendations for curriculum reform based upon the results.…”
Section: Introductionmentioning
confidence: 99%
“…This undermines education as a research field and likely has a negative impact on students.' (Newton, 2015) It is important to point out that the reports by Coffield et al (2004a;2004b) are nuanced, complex and resistant to reductionist soundbites and simplistic conclusions. Nevertheless, Coffield provided a succinct statement on learning styles in an opinion piece for the National Council for School Leadership:…”
Section: Learning Stylesmentioning
confidence: 98%
“…As scientists, physicians are trained to “view disease in a similar way to other natural phenomena” and as a result are oriented towards evidence in hierarchical terms in which “that which is most universal in its application or most general in its import, is the most significant” . The labelling of various medical theories, claims, practices or healing traditions as “myths” functions as a marker of senescence and progress in medical education . In the Kuhnian sense, myth busting is a natural operation of knowledge‐generating fields, whereby new scientific discoveries produce enough disjuncture in the current way of thinking to necessitate a paradigm shift to maintain the function of the field and to rid it of erroneous former explanations.…”
Section: The Etymology Of “Myth” and The Social Function Of Myth‐makingmentioning
confidence: 99%